Equilibrium yield curves under regime switching - Santiago García-Verdú (Banco de México, 2010)
This paper studies how inflation as a macroeconomic indicator affects nominal bond prices. I consider an economy with a representative agent with Epstein-Zin preferences. Regime switching affects the state-space capturing inêation and consumption growth. Thus, the agent is concerned about the intertemporal distribution of risk, which is affected by the persistence of the variables and the regimes. Regime switching allows for structural changes in the volatility of unexpected shocks. To the extent that inêationary unexpected shocks indicate lower consumption growth, nominal bond holders need to be compensated for these shocks. It follows that a switch in the regime state affecting the covariance of inflation and consumption growth can be interpreted as a change in the price of risk. I find coefficients of risk aversion from 40 to 90, and subjective discount factors above 0.99, depending on the exact specification of the model. The model yields have on average a positive slope, a consistent Principal Components decomposition, and predictability as in Cochrane and Piazzesi (2002).
Keywords: G12; E42; E43; E44; E31; 330; Consumption-based Asset Pricing; Regime Switching; Recursive Preferences; Yield Curve; Term Structure of Interest Rates; Kapitaleinkommen; Zinsstruktur; CAPM